Matrix Proof

  • #1
charlies1902
162
0
If A and B are n × n matrices, when does
(A + B)(A − B) = A^2 − B^2?

I guess I start out by expanding?

A^2 - BA-B^2+BA=0

Thus AB=BA in order for that to work?
 

Answers and Replies

  • #2
jbunniii
Science Advisor
Homework Helper
Insights Author
Gold Member
3,474
257
If A and B are n × n matrices, when does
(A + B)(A − B) = A^2 − B^2?

I guess I start out by expanding?

A^2 - BA-B^2+BA=0

Thus AB=BA in order for that to work?

Correct.
 

Suggested for: Matrix Proof

  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
6
Views
1K
  • Last Post
Replies
8
Views
3K
  • Last Post
Replies
3
Views
967
  • Last Post
Replies
9
Views
3K
  • Last Post
Replies
1
Views
2K
  • Last Post
Replies
5
Views
1K
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
3
Views
839
  • Last Post
Replies
5
Views
1K
Top